Jadidism movement in Ferghana - Ghulamov Husanboy (Zien Journals, 2022)
The emergence of Jadidism, the movement of progressives, the essence of Jadidism, the emergence of Jadidism in Bukhara, Khiva and Fergana valleys, the opening of Jadid schools, manifestations of Jadidism, the essence of the Jadidism movement.
Keywords: Modernism; Turkestan; Bukhara and Khiva; Crimea